Occupational asthma and allergy in snow crab processing in Newfoundland and Labrador. Issue 1 (6th September 2009) - Gautrin, D; Cartier, A; Howse, D; Horth-Susin, L; Jong, M; Swanson, M; Lehrer, S; Fox, G; Neis, B
Abstract : Background: Risk factors and prevalence of occupational asthma (OA) and occupational allergy (OAl) in the snow crab-processing industry have been poorly studied. Objective: To estimate the prevalence of OA and OAl in snow crab-processing workers and determine their relationship with exposure to snow crab allergens and other potential risk factors. Methods: A total of 215 workers (120 female/95 male) were recruited from four plants in Newfoundland and Labrador, Canada in 2001–2002. Results from questionnaires, skin-prick tests to snow crab meat and cooking water, specific IgEs against the latter, spirometry and peak flow monitoring were used to develop a diagnostic algorithm. An index based on work history and exposure measurements of snow crab aeroallergens was developed to estimate the cumulative exposure for each worker. Results: The prevalences of almost certain or highly probable OA and OAl were 15.8% and 14.9%, respectively. A high cumulative exposure to crab allergens, in jobs mostly held by women, was associated with OA (odds ratio (OR) = 14.0, 95% CI 3.0 to 65.8) (highest vs lowest Cumulative Exposure Index) and with OAl (OR = 7.1, 95% CI 1.9 to 29.0); job held when symptoms started (cleaning, packing, freezing) also predicted OA (OR = 3.9, 95% CI 1.6 to 8.7) and OAl (OR = 3.2, 95% CI 1.4 to 7.5). Atopy (OR = 2.8, 95% CI 1.2 to 6.8), female gender (OR = 10.7, 95% CI 3.6 to 32.1) and smoking were significant determinants for OA (OR = 3.1, 95% CI 1.3 to 7.4). Conclusions: The prevalences of OA and OAl are high in snow crab-processing workers of Canada's East Coast. Cumulative exposure to snow crab allergens was related to the prevalences of OA and OAl in a dose–response manner taking into account atopy, gender and smoking.